The cerebellum engages multiple pre-motor pathways through a divergent-convergent architecture to shape whisker dynamics - Bauer, Staf; Zhai, Peipei; van Wingerden, Nathalie; Zhao, Hehe; Romano, Vincenzo (Frontiers in Neural Circuits, 2026)
The cerebellar output can trigger whisker movement through indirect projections that pass via several brainstem pre-motor nuclei before reaching the facial nucleus, which directly controls whisker movements in rodents. Although the central pattern generator function of the intermediate reticular formation has been recently clarified, the roles of the other whisker pre-motor nuclei remain unclear. Here, we set out to compare the whisker movement kinematics of the main pre-motor whisker nuclei connecting the cerebellum and the facial nucleus. We optogenetically stimulated neurons located in the cerebellar cortex: Purkinje cells (PCs), the cerebellar nuclei (CN), the red nucleus (RN), the superior colliculus (SC), the spinal trigeminal nucleus (SV), and the reticular formation (RF); in head-fixed awake mice while monitoring the bilateral whisker movement. We show that optogenetic stimulation of the RN, SC, and SV resulted in a predominant midpoint change, whereas optogenetic stimulation of the PCs, CN, and RF resulted in faster whisker movements. In addition, the excitation of PCs, the RN, and SC resulted in symmetric bilateral whisking. In contrast, the excitation of the RF, and SV resulted in initial asymmetric movement, followed by a more dominantly symmetrical bilateral whisking. Importantly, PC excitation generated a robust rhythmic whisking pattern that could not be reproduced by direct CN stimulation, indicating that the cerebellar cortex sculpts CN population output rather than simply gating it. Our results suggest that cerebellar output engages multiple, specialized pre-motor pathways through a divergent-convergent architecture. This system allows different pre-motor nuclei to modulate distinct aspects of whisking kinematics, ultimately shaping whisker motor dynamics.